O poético alinhave de Murilo Mendes: o poeta, a musa e a metapoesia em As Metamorfoses - Antonio, Patrícia Aparecida; Pires, Antônio Donizeti [UNESP] (My University, 2010)
Lying under the contribution of a display of characteristics with multiple meanings (Catholicism, Surrealism, unite of contraries, and the dialogue with other types of art), Murilo Mendes focalizes some subjects that are made to become appealing in his works. Some of these subjects appear in his 1945’s poetry book, As metamorfoses, the object of analysis in this present work: the poet’s figure, insert in the historical view of the World War II and by the poet devastated; the muse’s figure, carrier of the sacred and the profane, whose body represents a repository of descriptions with surrealistic meanings, that is shown indistinctly as the poetry itself; and, concluding, the poetry (or the metapoetry) expressed in this context (historical and literary). Therefore, we intend to search, based in the analysis of poems, how each of this instances are configured inside the poetic universe of Murilo Mendes, with the intention of enlighten the constitution of the sewing made of them by the poet from Juiz de Fora; instances that are very precious when we deal with the poetry that gives to his writings the patent feature of modernity.

Valendo-se de um aparato de características de teor múltiplo (catolicismo, Surrealismo, unificação de contrários, dialogismo com outras artes), Murilo Mendes focaliza alguns temas que acabam por se tornar recorrentes em suas obras. São alguns desses temas, inseridos em seu livro de poemas de 1945, As metamorfoses, o objeto de análise do presente trabalho: a figura do poeta, de resto, inserido no panorama histórico da Segunda Guerra Mundial e por ele assolado; a figura da musa, portadora do sagrado e do profano, cujo corpo afigura-se como repositório das descrições de teor surrealista, e que se entremostra por vezes como a própria poesia; e, por fim, a poesia (ou a metapoesia) expressa nesse contexto (tanto histórico, quanto literário). Assim, pretendemos buscar, com base na análise de poemas, como cada uma dessas instâncias se configura dentro do universo poemático de Murilo Mendes, a fim de esclarecer em que se constitui o alinhave que delas é feito pelo poeta juiz-forano; instâncias tão caras quando se trata de poesia e que acabam por conferir a seus escritos um evidente caráter de modernidade.
Keywords: Modernismo brasileiro; Musa; Poeta; Metapoesia; Murilo Mendes; Literatura brasileira; Poesia lírica; Modernismo; Metapoesia